"Harmful to the commonality": the Luddites, the distributional effects of systems change and the challenge of building a just society. Issue 2 (9th February 2022) - McGowan, Katharine; Geobey, Sean
Abstract : Purpose: When complex social-ecological systems collapse and transform, the possible outcomes of this transformation are not set in stone. This paper aims to explore the role of social imagination in determining possible futures for a reformed system. The authors use a historical study of the Luddite response to the Industrial Revolution centred in the UK in the early-19th century to explore the concepts of path dependency, agency and the distributional impacts of systems change. Design/methodology/approach: In this historical study, the authors used the Luddites' own words and those of their supporters, captured in archival sources ( n = 43 unique Luddite statements), to develop hypotheses around the effects on political, social and judicial consequences of a significant systems transformation. The authors then scaffolded these statements using the heuristics of panarchy and basins of attraction to conceptualize this contentious moment of British history. Findings: Rather than a strict cautionary tale, the Luddites' story illustrates the importance of environmental fit and selection pressures as the skilled workers sought to push the English system to a different basin of attraction. It warns us about the difficulty of a just transition in contentious economic and political conditions. Social implications: The Luddites' story is a cautionary tale for those interested in a just transition, or bottom-up systems transformation generally as the deep basins of attraction that prefer either the status quo or alternate, elite-favouring arrangements can be challenging to shift independent of shocks. While backward looking, the authors intend these discussions to contribute to current debates on the role(s) of social innovation in social and economic policy within increasingly charged or polarized political contexts. Originality/value: Social innovation itself is often predicated on the need for just transitions of complex adaptive systems (Westley et al., 2013), and the Luddite movement offers us the opportunity to study the distribution effects of a transformative systems change – the Industrial Revolution – and explore two fundamental questions that underpin much social innovation scholarship: how do we build a just future in the face of complexity and what are likely forms those conversations could take, based on historical examples?